Determination of hemolysis, osmotic fragility and fluorescence anisotropy on irradiated red blood cells as a function of kV of medical diagnostic X-rays - M. Tungjai (2018)
Background: People occasionally undergo medical diagnosc X-ray examinaons and expose their red blood cells to radiaon. Radiaon that is generated from medical diagnosc X-ray machines is widely used in medical diagnoses. One of the important parameters is kilo-voltage (kV) that is applied across the X-ray tube in medical diagnosc X-ray machines. Kilo-voltage influences the radiaon dosage. The aim of this study is to determine the hemolysis, osmoc fragility, and fluorescence anisotropy value on irradiated red blood cells as a funcon of kV during medical diagnosc X-ray examinaons. Materials and Methods: The kV, kilo-voltage that is applied across an X-ray tube, of a medical diagnosc X-ray machine was operated at 50, 70 and 100 kV. We determined the hemolysis, osmoc fragility, and fluorescence anisotropy value in red blood cells at 0.5 and 4 hours post-irradiaon. In order to determine hemolysis and osmoc fragility, the release of hemoglobin was measured by spectrophotometry technique. 1,6-diphenyl-1,3,5-hexatriene (DPH) was used as a molecular probe for determining fluorescence anisotropy value by fluorescence anisotropy technique. Non-irradiated red blood cells served as the control. Results: For the 50, 70, and 100 kV of medical diagnosc X-rays, the hemolysis, osmoc fragility, and fluorescence anisotropy values of irradiated red blood cells at 0.5 and 4 hours post-irradiaon did not significantly change when compared to the control. Conclusion: Our results suggested that 50, 70, and 100 kV of medical diagnosc X -ray did not influence hemolysis, osmoc fragility, and fluorescence anisotropy values of irradiated red blood cells.